Pusat Pelatihan Bulu Tangkis Di Bangkinang Dengan Pendekatan Arsitektur Rumah Lontiok - Nurpela, Dian; Hidayat, Wahyu; Susilawaty, Mira Dharma (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Badminton is one of the most famous sport in the world. The development of badminton sport is growing rapidly in Indonesia after Indonesian’s declaration of independence. With development over time, this sport is already known in various areas, one of them is Kampar. The achievement of Kampar’s badminton athletes are also very good in various championships at the district, provincial, and national levels. But there is no sport venues that can accommodate the training of Kampar’s badminton athletes regulary and meet International standards, required a badminton training center that can facilitate such activities. The design of this training center uses the method of shape tansformation based on function and design theme. The concept used is speed and power on the potential. Is the most important thing in badminton, by taking one element that is smash. The smash characteristics applied to the building are sharp and fast. Implementation of both characters are also adapted to the architectural elements of the lontiok house, such us rectangular base form, facade and bulding circulation. The concept in line with the designing process in the making of Badminton Training Center in Bangkinang, Kampar, that meets the International Standards both in terms of quality and facilities. Keywords: Badminton, Training, Lontiok House